Simulation models in direct ophthalmoscopy education: A systematic review - Dutt, Deepaysh DCS; Hohnen, Harry; Kulshrestha, Subham; Razavi, Hessom (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Background: An ever-increasing range of simulation devices are available for direct ophthalmoscopy. However, the effectiveness of simulation design and components have not been evaluated. This systematic review aims to describe and evaluate direct ophthalmoscopy simulation models and highlight components that have been found to be effective, and challenges faced when using simulation models.Methods: A systematic review of the literature was conducted according to the PRISMA statement in four online databases: Medline, Embase, Cochrane Library and Web of Science. Citation searching using Google Scholar and Citationchaser was also undertaken. Validity and effectiveness were assessed using a validated scale based on Messick’s modern validity framework and McGaghie’s proposed levels of simulation-based translational outcomes respectively.Results: A total of 1,275 titles and abstracts were screened. A total of 37 studies were included in the final analysis. Physical models, digital models and virtual reality direct ophthalmoscopy models were described in studies. A plastic cannister design was the most common in the literature, followed by a sphere with a painted fundus and the EyeSi Direct Ophthalmoscope Simulator (VRmagic, GmbH, Mannheim, Germany). Simulation was effective in its ability to allow students to engage in repeated practice without patient discomfort. The lack of realism was the most noted limitation of simulation practice.Conclusion: While more robust evidence is needed to support simulation design efficacy in direct ophthalmoscopy, simulation-based teaching of direct ophthalmoscopy will likely be increasingly effective as technological advancements support improved realism and affordability.